2020
DOI: 10.1177/1533033820971660
|View full text |Cite
|
Sign up to set email alerts
|

Role of Human Epididymis Protein 4 (HE4) in Determining Survival of Patients With Endometrial Cancer: A Meta-Analysis

Abstract: Background: Human epididymis protein 4 (HE4) is a novel cancer biomarker. This study evaluates the prognostic role of HE4 in determining the survival of endometrial cancer patients. Methods: Literature search was conducted in electronic databases (Embase, Ovid, PubMed, Scopus, and Web of Science). Studies were selected if they reported the relationship between HE4 and the survival of endometrial cancer patients. Random-effects meta-analyses were performed to achieve estimates of baseline serum HE4 levels, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Subsequently, a further 34 articles were excluded for the following reasons: 13 presented insufficient data, 6 did not conduct meta-analysis, 4 explored outcomes that we were not interested in, 4 published not in English, the full text of 3 articles were not available, 2 published duplicated reports, 1 explored exposure that we were not interested in, and 1 conducted less than three original studies. Ultimately, 20 studies ( 7 , 8 , 15 , 19 22 , 42 54 ) were eligible to be included in the main analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a further 34 articles were excluded for the following reasons: 13 presented insufficient data, 6 did not conduct meta-analysis, 4 explored outcomes that we were not interested in, 4 published not in English, the full text of 3 articles were not available, 2 published duplicated reports, 1 explored exposure that we were not interested in, and 1 conducted less than three original studies. Ultimately, 20 studies ( 7 , 8 , 15 , 19 22 , 42 54 ) were eligible to be included in the main analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 showed the nine meta-analyses that involved 81 original studies in four articles for prognosis ( 8 , 44 , 51 , 54 ). These 4 articles were published between 2017 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Dai et al conducted a meta‐analysis of 29 studies on HE4 expression and tumor survival outcome and found that high HE4 expression was associated with poorer OS (HR = 2.15, 95% CI: 1.77–2.62, p < 0.001), and this association was not affected by race or tumor type (EC, ovarian cancer, lung cancer) 4 . He et al performed a meta‐analysis of nine studies on HE4 expression and survival outcomes of EC and found that 5‐year survival was higher in patients with low HE4 concentrations, the pooled HRs analysis showed that high HE4 levels were associated with shorter survival in patients with EC 5 . In our study, we found that high serum HE4 levels were associated with poorer OS and DFS, and in a subgroup analysis, only multivariate analysis model results showed no correlation between high serum HE4 levels and poor OS in non‐occident.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more studies have reported the evolving role of HE4 in monitoring EC progression and prognosis, but there is heterogeneity in study results and a meta‐analysis is needed. Meta‐analyses regarding HE4 and prognostic value by Dai et al and He et al both found that higher HE4 levels were significantly associated with poorer survival 4,5 . However, these meta‐analyses only investigated the prognostic value of HE4 and did not analyze preoperative HE4 levels/expression in relation to postoperative pathologic factors, so the purpose of this meta‐analysis was to explore the relationship between HE4 expression in serum and tissue and postoperative pathological factors and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Human epididymis protein 4 (HE4) has been reported to act as a fibroblast-derived mediator of renal fibrosis [ 10 , 11 ]. Zhang et al reported that hypoxia-induced HE4 promotes extracellular matrix accumulation and renal fibrosis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%